Bitter melon (Momordica charantia) fruit extract ameliorates methotrexate-induced reproductive toxicity in male rats - ŞEN, ALİ; ÖZBEYLİ, DİLEK; ERCAN, FERİHA; ŞENER, GÖKSEL (MARMARA UNIV, FAC MEDICINE, 2021)
Objective: Methotrexate (MTX) is a drug commonly used for the treatment of malign neoplastic and inflammatory diseases. Anti-oxidant and anti-inflammatory effects of bitter melon (BM) were reported. The aim of this study was to examine the effects of BM fruit extract on MTX-induced testicular and epididymal damage. Materials and Methods: Sprague Dawley male rats were divided into three groups (n=8) as control, MTX and MTX+BM. A single dose of MTX (20 mg/kg) was injected intraperitoneally to the MTX and MTX+BM groups. BM fruit extract (600 mg/kg) was applied to the MTX+BM group orally for 5 days. Testes were examined for general histopathology, proliferating and apoptotic cells. The epididymis samples were used for the evaluation of sperm morphology. Oxidative and inflammatory markers were analysed biochemically. Results: Increased abnormal spermatozoa, degenerated seminiferous tubules with increased apoptotic cells and decreased proliferative cells were observed in the MTX group. TNF-alpha, IL-1 beta, 8-hydroxy-2-deoxyguanosine and caspase-3 levels increased, superoxide dismutase and catalase levels decreased in both testis and epididymis samples. All these histological and biochemical parameters were ameliorated in the MTX+BM group. Conclusion: Methotrexate causes testis damage by decreasing spermatogenic cells and increasing apoptosis through oxidative stress and inflammation. BM extract improves testis and epididymis damage with its possible anti-oxidant and anti-inflammatory effects.
Keywords: Methotrexate; Bitter melon; Testis; Epididymis; Oxidative stress; GROWTH; INJURY; MAP30